Pembangunan Sistem Transaksi Penjualan Barang dan Jasa (Studi Kasus: Startup Botanis Kota) - Heykhal Hafiddhan Rachman; Denny Sagita Rusdianto; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Startups are business entities that have a small scope. Nevertheless, startups are not free from some problems. One of them is the Botanis Kota Startup. This startup has a problem with the division of work duties, which is mostly done by business owners. With a website to make transactions and orders, it is hoped that it can reduce the owner's workload. The steps taken in conducting this research use the Waterfall software research method. This research begins with a literature study, then conducts requirements engineering for the system, system design, system implementation, and system testing. In requirement elicitation step, the results obtained are system requirements consisting of 42 functional requirements and 1 non-functional requirement. Next, the design results in a software design that is made in accordance with the needs of the needs analysis. After the design is complete, implementation is carried out with the PHP programming language using the YII framework and MySQL database. At testing stage, the results obtained from unit testing using the highest cyclomatic complexity is worth 10 and the function test of 3 sample components and software integration is 100% valid, then validation testing of 42 functional requirements and 100% valid value, then compatibility testing found there were minor problems that did not affect the main functions in Safari and Firefox browsers. The results of the tests carried out, the system built has met the requirements of functional and non-functional needs of the problems found in the case study taken at Botanis Kota Startup.